Evaluation of a single cycle influenza virus as a candidate vaccine - Sadler, H (2021)
Influenza A continues to impose a considerable burden on humans and animals, including farmed poultry and pigs. Current vaccination approaches successfully protect certain populations against specific strains, but none are effective at consistently inducing broad and long-lasting protection to the diversity of circulating strains.